Knowledge Management The Development Of State Civil Apparatus In Polewali Mandar Regency, West Sulawesi Province - Tri Ayu Hardiyanti; Fernandes Simangunsong; Layla Kurniawati (Sean Institute, 2024)
The aim of this research is to find out and analyze Knowledge Management in the Development of the State Civil Apparatus, find out and analyze the supporting and inhibiting factors of Knowledge Management in the Development of the State Civil Apparatus in Polewali Mandar Regency, West Sulawesi Province. The theory used as an analytical tool in writing this thesis is Nonaka and Takeuchi's theory in Nawawi (2010) which explains that knowledge management requires 4 (four) stages (known as SECI), namely